Understanding cultural determinants of Scientific-Knowledge Development: empirical conceptualization from a cross-country investigation - Yong, Enn Lun (Springer, 2020)
The purpose of this paper is to test three hypotheses with regard to the development of scientific knowledge in relation to cultural dimensions. Two empirical models are formed to identify the causal effects of the cultural dimensions on scientific-knowledge development. The three hypotheses are tested in a case study consisting of 74 countries. Robust standard-error regressions are presented. The results show that the degree of egalitarian and hierarchical ethos across countries aids the growth of scientific knowledge. The empirical evidence complements new insights to the hypothesis of individualism-induced innovation. The evidence in this paper shows that the positive effect of individualism on the growth of scientific knowledge is also considerably lower than that of an egalitarian and hierarchical system. The proposition in this paper shows new insight into the economic and institutional evolution rooted in universal values of culture. As the world economy has been burdened by the enormous inequality of development, cultivating awareness of the competitive advantage hidden in cultural values is an essential prescription for advancing development policy pertaining to knowledge.